The total length of spindle microtubules depends on the number of chromosomes present (The Rockefeller University Press, 1985)
We extracted chromosomes by micromanipulation from Melanoplus differentialis spermatocytes, producing metaphase spindles with only one or a few chromosomes instead of the usual complement of 23. Cells with various numbers of chromosomes were prepared for electron microscopy, and spindle microtubule length was measured. A constant increment of microtubule length was lost upon the removal of each chromosome; we estimate that only approximately 40% of the original length would remain in the total absence of chromosomes. Unexpectedly, kinetochore microtubules were not the only ones affected when chromosomes were removed: nonkinetochore microtubules accounted for a substantial fraction of the total length lost. No compensatory increase in microtubule length outside the spindle was found. Studies by others show that the kinetochore microtubules of extracted chromosomes are left behind in the cell and dissassemble. The resulting increase in subunit concentration would be expected from in vitro studies to drive microtubule assembly until the original total microtubule length was restored, but that did not happen in these living cells. We conclude that the assembly of a certain, large fraction of microtubule subunits into stable microtubules is dependent on the presence of chromosomes. Possible explanations include (a) limits on microtubule length that prevent any net assembly of the subunits released after chromosomes are removed or (b) a promotion of microtubule assembly by chromosomes, which therefore is reduced in their absence. Chromosome-dependent regulation of microtubule length may account for some features of normal mitosis.